Assessment of barriers to public rental housing exits: Evidence from tenants in Beijing, China. (April 2019) - Li, Jintao; Stehlík, Milan; Wang, Yi
Abstract: Public rental housing (PRH) exits exert a profound influence on turnover rates, which further impact the public housing principles of fairness and efficiency. However, very few studies have attempted to investigate the tenant's barriers to exit PRH units in Chinese studies. In this paper, using data drawn from a randomly sampled survey of tenants in Beijing during the March 2017, we employ structural equation modeling (SEM) to examine the factors influencing tenant's barriers to exit. We find that housing availability is the most influential factor in determining the tenant's barriers to leave PRH, and residential satisfaction is also considered as a motivation against PRH exits. In addition, residential satisfaction transfers the impact of tenant's perceptions of housing and neighborhood to exit barriers. Especially, the effects of housing availability on exit barriers are higher in some groups, such as elderly, high income households, large-sized families and respondents with long spell of residence. Any program aimed at getting tenants to leave public housing sector needs to reduce their barriers to access to the private rental market and take into consideration the various characteristics of the tenants. Highlights: Explored the determinants of tenants' barriers to exit public rental housing in Beijing, China. Housing availability is the most influential factor in determining the tenant's barriers to leave public rental housing. Residential satisfaction transfers the impact of tenant's perceptions of housing and neighborhood to exit barriers. Effects of housing availability on exit barriers are higher in some families.